2021
DOI: 10.1155/2021/5529540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unidirectional In Situ Stress on Crack Propagation of a Jointed Rock Mass Subjected to Stress Wave

Abstract: This paper proposes a large-scale experiment combined with multiple cement mortar blocks to simulate stress wave propagation across a jointed rock mass under unidirectional in situ stress. Two identical mortar block models with smooth, dry, and unfilled joints were poured. The stress waves in Model 1 and Model 2 were generated by an electric spark source and a blast-induced source, respectively. The effects of these two excitation sources on stress wave propagation were compared through crack propagation exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Our case study area is in Fuxin City, Liaoning Province, China where many buildings are between 20 and 30 years old, are located in urbanized areas or suburbs, and experience uneven foundation settlement. Natural changes in groundwater levels are exacerbated by anthropogenic activities which have caused and accelerated soil liquefaction, resulting in foundation settlement (Fan and Cai 2021). In recent years, several meter-long cracks have emerged in building foundations and at the lower level of walls.…”
Section: Foundation Settlement and Problem Formulation Foundation Set...mentioning
confidence: 99%
“…Our case study area is in Fuxin City, Liaoning Province, China where many buildings are between 20 and 30 years old, are located in urbanized areas or suburbs, and experience uneven foundation settlement. Natural changes in groundwater levels are exacerbated by anthropogenic activities which have caused and accelerated soil liquefaction, resulting in foundation settlement (Fan and Cai 2021). In recent years, several meter-long cracks have emerged in building foundations and at the lower level of walls.…”
Section: Foundation Settlement and Problem Formulation Foundation Set...mentioning
confidence: 99%
“…Peng et al [27] found that high ground temperature and ground stress had a significant influence on the cracking mode of the surrounding rock of the hydraulic tunnel. Fan et al [28] used LS-DYNA to explore the crack growth of jointed rock mass under different ground stresses and verified that in-situ stress has an obvious guiding effect on crack growth.…”
Section: Introductionmentioning
confidence: 99%
“…In southwest China, landslides are among the most devastating natural disasters, causing damage to life, property, and local infrastructure (Aggarwal et al, 2020;Fan & Cai 2021;Zhou et al, 2021). Over 7,000 landslides occurred in China in 2016 as reported in the annual report provided by the China Institute of Geo-Environment Monitoring (Tang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%